Enhanced photoelectrochemical water splitting of CrTiO2 nanotube photoanodes by the decoration of their surface via the photodeposition of Ag and Au. Issue 33 (8th August 2018) - Sharifi, Tayebeh; Ghayeb, Yousef; Mohammadi, Tecush; Momeni, Mohamad Mohsen
Abstract : Photoelectrochemical water splitting of CrTiO2 nanotube arrays decorated with loading-controllable Ag and Au by the photodeposition method. Abstract : It is of great significance to develop green fuels in order to prevent the accumulation of carbon dioxide generated by the combustion of conventional fossil fuels. A potential, clean, renewable alternative fuel, which may be produced from solar energy, stored and safely transported, is hydrogen. In this work, bare CrTiO2 NTs were fabricated using an in situ anodizing process. CrTiO2 NTs were then modified with the photodeposition of noble metals (Ag and Au) at different light irradiation times (10–120 min). The new photocatalysts have been characterized using SEM, EDX, XRD, Raman and UV-vis spectra. The impact of noble metals on the photo-electrochemical activities of the photocatalysts has been evaluated. In addition, electrochemical impedance spectroscopy was conducted for the semiconductor/electrolyte interface. Most of the current density is related to Ag4/CrTiO2 NTs and Au4/CrTiO2 NTs, and is nearly 2 and 3 times as that of the bare CrTiO2 NTs, respectively. All of the samples have adequate stability during continuous illumination for 1200 s. Finally, water splitting was performed under light irradiation at 0.6 V vs. Ag/AgCl for 60 min. Ag4/CrTiO2 NTs and Au4/CrTiO2 NTs have the highest H2 evolution among their families, corresponding to 0.52 and 0.80 ml cm −2 h −1, respectively.